Comparison of adsorption equilibrium models and error functions for the study of sulfate removal by calcium hydroxyapatite microfibrillated cellulose composite. Issue 8 (18th April 2018) - Hokkanen, Sanna; Bhatnagar, Amit; Koistinen, Ari; Kangas, Teija; Lassi, Ulla; Sillanpää, Mika
ABSTRACT: In the present study, the adsorption of sulfates of sodium sulfate (Na2 SO4 ) and sodium lauryl sulfate (SLS) by calcium hydroxyapatite-modified microfibrillated cellulose was studied in the aqueous solution. The adsorbent was characterized using elemental analysis, Fourier transform infrared, scanning electron microscope and elemental analysis in order to gain the information on its structure and physico-chemical properties. The adsorption studies were conducted in batch mode. The effects of solution pH, contact time, the initial concentration of sulfate and the effect of competing anions were studied on the performance of synthesized adsorbent for sulfate removal. Adsorption kinetics indicated very fast adsorption rate for sulfate of both sources (Na2 SO4 and SLS) and the adsorption process was well described by the pseudo-second-order kinetic model. Experimental maximum adsorption capacities were found to be 34.53 mg g −1 for sulfates of SLS and 7.35 mg g −1 for sulfates of Na2 SO4. The equilibrium data were described by the Langmuir, Sips, Freundlich, Toth and Redlich–Peterson isotherm models using five different error functions.